2021
DOI: 10.36941/ajis-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture as a Mediator Motivation and Transformational Leadership on Employee Performance

Abstract: The research process begins by identifying problems in the Ministry of Public Works and Public Housing (PUPR) of the Republic of Indonesia. These several targets were not achieved by the end of 2019, sorting and conducting problem formulation, data collection, and preliminary studies. This process starts from January 2020 to May 2020. Following the research objectives, the research design used was a descriptive causal study with the variable Motivation, Transformational Leadership, and Organizational Culture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 49 publications
(55 reference statements)
1
13
0
3
Order By: Relevance
“…As a result, employees at work want the organization to restore a balance between their contribution and the work situation (Giauque et al, 2012). Measurement of work motivation determines the goals, behavioral persistence, and work-related intensity desired by the organization (Virgiawan et al, 2021;Arshadia, 2010). Situational stimuli, personal preferences, and also interactions can determine a person's motivation in pursuing a desired goal.…”
Section: Work Motivationmentioning
confidence: 99%
“…As a result, employees at work want the organization to restore a balance between their contribution and the work situation (Giauque et al, 2012). Measurement of work motivation determines the goals, behavioral persistence, and work-related intensity desired by the organization (Virgiawan et al, 2021;Arshadia, 2010). Situational stimuli, personal preferences, and also interactions can determine a person's motivation in pursuing a desired goal.…”
Section: Work Motivationmentioning
confidence: 99%
“…Both internal and external strategies have been developed to inspire and persuade employees to perform better in recent years. To increase employee performance, organizations are now implementing high-performance human relations preparation and planning (Virgiawan et al, 2021). Consequently, work-life balance has become a crucial component of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study on leadership must consider the correlations between variables at different levels. The existing studies have shown that the transformational leadership could affect the dependent variables such as intention of resignation and OCB (Virgiawan et al, 2021 ), and could affect the organizational contextual variables (Saira et al, 2021 ). Therefore, through multi-level research, employees' perceptions of leaders can be aggregated to the group level and their relationship with organizational commitment can be tested (Tremblay et al, 2019 ).…”
Section: Hypotheses Developmentmentioning
confidence: 99%